Érosion de la biodiversité marine, méprise ou réalité : le cas des invertébrés marins benthiques en Manche (Atlantique Nord-Est) - Jean-Claude Dauvin (VertigO)
The erosion of biodiversity and marine diversity is biased because it is based mainly on vertebrates from tropical or island areas; it does not apply to marine invertebrates. The invertebrate diversity is high in the English Channel, and increases according to new studies and the voluntary or involuntary introductions of non-native species. The benthic fauna is more diverse than pelagic fauna shows resistance capacities to human disturbances and especially a strong capacity of resilience, allowing when a disturbance ceases, to find a fauna nearby close to that pre-existing before disturbance. Some populations appear temporary because they are sporadically alimented by larvae transports under the effect of winds that are more variable than the predictable tidal currents. While some populations show reductions according to the decrease in areas favourable to their development, others show increases, especially in connection with global warming favourable to their reproduction. Several examples of change in species distribution areas are proven; however, no disappearance of invertebrate populations or species is known.